Synthesis and Investigation of Albumin Nanoparticles Loaded With Anti-Tuberculosis Drug Isoniazid - Galiyeva, A.; Tazhbayev, Ye.; Zhumagaliyeva, T.; Karimova, B.; Tabriz, N.; Khutoryanskiy, V.V. (Biopolymers, 2025)
The development of novel treatment strategies for tuberculosis (TB), including its multidrug-resistant forms, remains a global health priority. Conventional first-and second-line anti-TB drugs are often incorporated into polymer-based delivery systems to improve efficacy and reduce side effects. Among biodegradable, non-toxic, and biocompatible polymers, human serum albumin (HSA) stands out as a highly promising drug carrier. In this study, isoniazid (INH)-loaded human serum albumin nanoparticles were synthesized via the reaction of HSA macromolecules with cysteine in the presence of urea. Key nanoparticles characteristics— including size, polydispersity, drug loading efficiency, and drug binding capacity—were systematically evaluated and optimized. The effects of various formulation parameters, such as solution pH and concentration of urea, cysteine, albumin, and isoniazid, were investigated. Conformational changes in the protein structure were assessed using spectrofluorometric analysis. Additionally, the physicochemical properties and in vitro drug release profiles of HSA-INH nanoparticles were characterized. The antimicrobial activity of the nanoparticles was tested against the wild-type Mycobacterium tuberculosis H37Rv strain at isoniazid concentrations of 5, 25, and 50 mg/mL. The minimum inhibitory concentration of isoniazid when delivered via HSA nanoparticles was also determined.
Keywords: albumin; cysteine; isoniazid; nanoparticles; urea